Medication persistence of HIV-infected drug users on directly administered antiretroviral therapy. - Ing, Eileen C; Bae, Jason W; Maru, Duncan Smith-Rohrberg; Altice, Frederick L (AIDS and behavior, 2013)
Patient and regimen persistence in HIV-infected drug users are largely unknown. We evaluated patterns of medication non-persistence among HIV-infected drug users enrolled in a prospective, 6-month randomized controlled trial of directly administered antiretroviral therapy (DAART). Medication-taking behavior was assessed via direct observation and MEMS data. Of 74 participants who initiated DAART, 59 (80%) subjects were non-persistent with medication for 3 or more consecutive days. Thirty-one participants (42%) had 2 or more episodes of non-persistence. Higher depressive symptoms were strongly associated with non-persistence episodes of ≥ 3 days (AOR: 17.4, P = 0.02) and ≥ 7 days AOR: 5.4, P = 0.04). High addiction severity (AOR 3.2, P = 0.03) was correlated with non-persistence ≥ 7 days, and injection drug use (AOR: 15.2, P = 0.02) with recurrence of non-persistence ≥ 3 days. Time to regimen change was shorter for NNRTI-based regimens compared to PI-based ones (HR: 3.0, P = 0.03). There was no significant association between patterns of patient non-persistence and virological outcomes.
Keywords: Adult; Anti-HIV Agents; Antiretroviral Therapy, Highly Active; Behavior, Addictive; CD4 Lymphocyte Count; Connecticut; Directly Observed Therapy; Drug Users; Female; HIV Infections; Humans; Interviews as Topic; Kaplan-Meier Estimate; Male; Medication Adherence; Proportional Hazards Models; Randomized Controlled Trials as Topic; RNA, Viral; Severity of Illness Index; Substance Abuse, Intravenous; Treatment Outcome; Viral Load